Risk assessment of Gibberella circinata for the EU territory and identification and evaluation of risk management options - EFSA Panel on Plant Health (PLH) (EFSA Journal, 2010)
Abstract The Panel on Plant Health was asked to provide a risk assessment for Gibberella circinata Nirenberg and O'Donnell, for the EU territory, and to identify and evaluate effectiveness of risk management options in reducing the risk posed by the organism. G. circinata is presently not listed in Council Directive 2000/29/EC. Outbreaks of the organism have been reported in EU (in Spain, Italy, France and Portugal). The risk assessment indicates that, in parts of the European Union, there is risk of pitch canker affecting the host species (pine and Douglas‐fir). Entry into and spread within the European Union are considered very likely. The organism has a very high potential for establishment. The following pathways for entry have been identified: contaminated seed and other propagation material, different forms of wood material, plant material for decorative purposes, soil and growing substrates, natural means (wind, wind‐blown rain, insects and other animals carrying spores) and human activities. Based on host distribution and climatic conditions, the potentially endangered areas include wide areas of central and northern Portugal, northern and eastern Spain, south and coastal areas of France, coastal areas of Italy and parts of the coastal areas of Greece. In these areas, pine forests, including plantations and native forest, cover over 10 million hectares. Host species are also widely used as ornamentals. The potential consequences of pitch canker in the endangered areas are considered massive. At present there is no single means of controlling pitch canker. Consequently, an integrated disease management approach, which combines appropriate nursery and silvicultural practices, should be used to reduce the impact of the disease. The current legislation, including the provisional emergency measures (Commission Decision 2007/433/EC), is aimed at limiting the introduction of the organism but it may have only a limited effect on its spread.